Switching tests of an experimental vacuum circuit breaker - Valery Aleksandrovich Lavrinovich; Boris Innokentievich Ubiennykh; Andrey Aleksandrovich Kladko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2016)
Relevance of the work is caused by the active ongoing technical re-equipment of electric networks medium voltage at oil and gas enterprises of the Russian Federation. High operational reliability, environmental friendliness and ease of maintenance make the vacuum circuit breaker the most preferred switchgear for industrial conditions inherent in the mining industry enterprises. Like any other industrial equipment, the vacuum circuit breaker must meet certain characteristics, controlled both during the pre-operational testing and at operation. In this regard, the preliminary tests on the prototypes of the switching capacity of the vacuum switches during their design are not only relevant but necessary task. The main aim of the study is the experimental determination of the switching characteristics of the vacuum interrupters as a part of the high-voltage vacuum circuit breaker with a rated voltage of 10 kV. The methods. To determine the switching characteristics of the investigated high-voltage vacuum circuit breaker the authors have applied the synthetic test circuit by Vale-Dobker, forming on the test object the fault current in the range from 1 to 10 kA and transient recovery voltage across the contacts of the vacuum chamber up to 20 kV. The results. The authors studied the breaking capacity of the experimental vacuum interrupters as a part of the vacuum circuit breaker for fault current range of 1...10 kA. It was determined that the experimental vacuum interrupters successfully switch off the current to 18,3 kA at transitional recovery voltage of 0,85 kV, but they are not suitable for switching networks with rated breaking current of 10 kA at transitional recovery voltage characteristic of the voltage class switches of 10 kV. It is shown that series connection of two vacuum interrupters in each pole of the vacuum circuit breaker is necessary for applying the experimental vacuum interrupters in the networks of 10 kV voltage class.